Winnie the Pooh - Milne, A. A. (Alan Alexander), 1882-1956; Shepard, Ernest H. (Ernest Howard), 1879-1976 (New York : Puffin Books, 1992)
The adventure of Christopher Robin and his friends, in which Pooh Be ar uses Balloon to get honey, Piglet meets a Haffalump, and Ecyore h as a birthday